The measure of a man - Johnstone, William W. (Pinnacle Books, Kensington Publishing Corp., 2022)
In "Law of the Mountain Man," Smoke Jensen must return to the gun when he accidentally rides into the middle of the biggest range war of the decade; and in "War of the Mountain Man," Jensen must rescue his wife Sally, who has been kidnapped by the cutthroat who runs Hell's Creek.